PERIODIZATION OF THE TRAINING PROCESS: COMPARATIVE ANALYSIS OF TWO MODELS THROUGH THE PRISM OF MODERN RESEARCH ПЕРИОДИЗАЦИЯ ТРЕНИРОВОЧНОГО ПРОЦЕССА: СРАВНИТЕЛЬНЫЙ АНАЛИЗ ДВУХ МОДЕЛЕЙ ЧЕРЕЗ ПРИЗМУ СОВРЕМЕННЫХ ИССЛЕДОВАНИЙ (Rehabilitation and Recreation, 2018)
In this article, two known models of the periodization of the training process are compared: linear and wave. Their effectiveness is analyzed from the point of view of various variables. The narrative review presented in detail examines all the experimentally conducted science works and thereby allows readers to broaden their horizons on this topic. The strengths and weaknesses of both periodic models were identified and outlined.